(untitled) (Mongolian Journal of Agricultural Sciences, 2018)
The sustainable development strategy of the crop to implement environmental sustainability to be economically efficient, directed to improve soil productivity of the field and to increase the amount of harvest and to fully supply needs of food production by using research analysis. There are many types of methods for hypothesis testing in mathematical and statistical analyses. From these methods, T-stat and F-stat are widely used. However, they are in sufficient to express the final results, therefore we suggest to use Wald test, Variables test and Reset test. In addition to the quality of soil, wheat harvest also affects many factors, including climate, landscape, technology, and ecology. May-August precipitation (mm) and average air temperature (0C), the number of sunspot activation and the amount of crop in the Central region 1970-2015 are selected and converted to standardized average values, and done correlation coefficients analysis and multiple-factor regression analysis, hypotheses and tests. The assumptions should be regularly reviewed and verified to eliminate uncertainties in the reliability of quantitative data in agricultural research and analysis. The following conclusions have been made to examine Wald test, Variables test, and Reset test hypotheses based on the Central and Regional Weather data. The main factors that increase wheat harvest are the amount of precipitation. The precipitation is recognized for all assumptions. Other indicators (wind speed, landscape etc.) need to be selected rather than average air temperature in harvest. Хөдөө аж ахуйн тоон мэдээлэлд таамаглал дэвшүүлж, шалгах Хураангуй: Ургамал өсч хөгжих, ургац бүрэлдэх үйл явц нь гадаад орчны олон хүчин зүйлийн шууд нөлөөгөөр ургамалд явагдах тодорхой биологи, физиологи, биофизик, зарим талаар биохимийн хуулиудад ямар нэгэн байдлаар захирагддаг. Ургамал ургах, ургац бүрэлдэх явцыг дээрх хуулиудын хүрээнд авч үзэхдээ ургамал болон түүний хүрээлэн буй орчны хоорондох зүй тогтлыг математик, статистикийн аргаар илэрхийлж, ургамалын ургах бүхий л үйл явцыг загварчлах боломжтой. ХАА-н судалгаанд түүврийн тоо мэдээнд тулгуурласан параметр нь эх олонлогийг төлөөлж чадах эсэх талаар таамаглал дэвшүүлж, шалгах шаардлага зайлшгүй тулгардаг. Математик, статистикийн шинжилгээнд таамаглал дэвшүүлж, шалгах олон төрлийн арга байдгаас Стьюдентийн шинжүүрээр, Фишерийн шинжүүрийг өргөн ашигладаг ба эдгээр нь эцсийн үр дүнг илэрхийлэхэд хангалтгүй, тиймээс Wald test, Variables test, Reset test ашиглах шаардлагатай. Түлхүүр үг: Хамаарлын шинжилгээ, загварын ач холбогдол, хувьсагчдын шалгуур